2021
DOI: 10.1075/itl.21001.alo
|View full text |Cite
|
Sign up to set email alerts
|

The effect of input modes and number of exposures on the learning of L2 binomials

Abstract: Despite the importance of mastering different types of formulaic sequences in a second language, little is known about the relative effect of different input modes on their acquisition. This study explores the learning of a particular type of formulaic language (binomials) in three input modes (reading-only, listening-only, and reading-while-listening) at different frequencies of exposure (2, 4, 5 and 6 occurrences). Arabic learners of English were presented with three stories, each in a different mode, that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
(79 reference statements)
1
6
2
Order By: Relevance
“…Thus, it seems to be the case that whilst nonnatives did register co-occurrence restrictions in terms of which words go together, they did not register the configuration/order of the words. This lack of a configuration effect stands in contrast with findings of Alotaibi et al (2022) who found that nonnative Arab learners of English were able to develop sensitivity to the preferred order of binomials (similar to existing phrases) after six exposures. It should be noted, however, that unlike the present study, Alotaibi et al (2022) included higher frequency levels (up to six occurrences) than the present study (with a maximum of four encounters) and employed declarative post-treatment measures.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Thus, it seems to be the case that whilst nonnatives did register co-occurrence restrictions in terms of which words go together, they did not register the configuration/order of the words. This lack of a configuration effect stands in contrast with findings of Alotaibi et al (2022) who found that nonnative Arab learners of English were able to develop sensitivity to the preferred order of binomials (similar to existing phrases) after six exposures. It should be noted, however, that unlike the present study, Alotaibi et al (2022) included higher frequency levels (up to six occurrences) than the present study (with a maximum of four encounters) and employed declarative post-treatment measures.…”
Section: Discussioncontrasting
confidence: 99%
“…This lack of a configuration effect stands in contrast with findings of Alotaibi et al (2022) who found that nonnative Arab learners of English were able to develop sensitivity to the preferred order of binomials (similar to existing phrases) after six exposures. It should be noted, however, that unlike the present study, Alotaibi et al (2022) included higher frequency levels (up to six occurrences) than the present study (with a maximum of four encounters) and employed declarative post-treatment measures. Sonbul and Schmitt (2013) found a dissociation between gains in declarative (paper-and-pencil) tests and those reflecting online performance.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations